The Neutrophil-to-Lymphocyte Ratio as a Surrogate Marker for Disease Activity in Systemic Lupus Erythematosus: A Correlation Study Using the SLE-DAS - Ming Yan Wong; Chi Chiu Mok (Journal of Clinical Rheumatology and Immunology)
Background: Systemic lupus erythematosus (SLE) is a multisystem autoimmune disorder mainly affecting women of childbearing age. Mortality and organ damage of SLE is mainly due to uncontrolled disease activity and treatment-related toxicities. Thus, assessment of disease activity is important during routine clinical practice. In recent years, neutrophil-to-lymphocyte ratio (NLR) has been explored as a marker of disease in many autoimmune disorders including SLE. As such, our study objective is to investigate the correlation between neutrophil-to-lymphocyte ratio (NLR) and disease activity of SLE using the SLE disease activity score (SLE-DAS) in our local population. Methods: Consecutive adult patients who fulfilled the ACR or SLICC criteria for SLE were recruited between March 2023 and February 2024. SLE activity was assessed by SLE-DAS, physicians’ global assessment (PGA) and SLE disease activity index-2000 (SLEDAI-2K). The calculated NLR was correlated with disease activity indices and serological parameters (anti-dsDNA, C3/4) by Spearman’s rank correlation. Patients were stratified into remission, low and moderate/severe disease activity as defined by the SLE-DAS and comparison of the NLR was performed among these subgroups by one-way ANOVA. Results: A total of 420 SLE patients were studied (96.2% women, age 46.0± 11.0 years, SLE duration 16.4± 8.3 years). Moderate/severe, low disease activity and SLE-DAS remission was present in 70(16.7%), 66(15.7%), and 284(67.6%) patients, respectively. SLE-DAS correlated significantly with SLEDAI-2K (rho 0.9; p<0.001) and PGA (Rho 0.60; p<0.001). The mean NLR of all patients was 3.54± 4.0 and NLR correlated significantly with SLE-DAS (Rho 0.17; p<0.001). The NLR was significantly higher in active renal (urine P/Cr >0.5, active sediments or histological features) than inactive SLE (4.62 vs 3.27; p=0.02). The NLR in patients with moderate/severe SLE-DAS activity was significantly higher than those in remission (4.87 vs 3.27; p=0.007). ROC analysis showed that a NLR cut-off of 3.11 showed a sensitivity of 55.6% and specificity of 68.7% in detecting moderate/severe SLE-DAS (AUC 0.67[0.6-0.7]; p<0.001). Conclusion: The NLR is a satisfactory and convenient marker that correlates significantly with disease activity in SLE.